Peripheral PD-1+CD56+ T-cell frequencies correlate with outcome in stage IV melanoma under PD-1 blockade - Bochem, Jonas; Zelba, Henning; Amaral, Teresa; Spreuer, Janine; Soffel, Daniel; Eigentler, Thomas; Wagner, Nikolaus Benjamin; Uslu, Ugur; Terheyden, Patrick; Meier, Friedegund; Garbe, Claus; Pawelec, Graham; et al. (PLoS ONE, 2019)
Immune checkpoint blockade with anti-PD-1 antibodies is showing great promise for patients with metastatic melanoma and other malignancies, but despite good responses by some patients who achieve partial or complete regression, many others still do not respond. Here, we sought peripheral blood T-cell biomarker candidates predicting treatment outcome in 75 stage IV melanoma patients treated with anti-PD-1 antibodies. We investigated associations with clinical response, progression-free survival (PFS) and overall survival (OS). Univariate analysis of potential biological confounders and known biomarkers, and a multivariate model, was used to determine statistical independence of associations between candidate biomarkers and clinical outcomes. We found that a lower than median frequency of peripheral PD-1+CD56+ T-cells was associated with longer OS (p = 0.004), PFS (p = 0.041) and superior clinical benefit (p = 0.009). However, neither frequencies of CD56-CD4+ nor CD56-CD8+ T-cells, nor of the PD-1+ fraction within the CD4 or CD8 subsets was associated with clinical outcome. In a multivariate model with known confounders and biomarkers only the M-category (HR, 3.11; p = 0.007) and the frequency of PD-1+CD56+ T-cells (HR, 2.39; p = 0.028) were identified as independent predictive factors for clinical outcome under PD-1 blockade. Thus, a lower than median frequency of peripheral blood PD-1+CD56+ T-cells prior to starting anti-PD-1 checkpoint blockade is associated with superior clinical response, longer PFS and OS of stage IV melanoma patients.
CRIS-Team Scopus Importer:2019-08-27